TEKNOLOGI PENGERING PADI UV DRYER KAPASITAS 10 TON UNTUK KETAHANAN PANGAN DI KAMPUNG MARGA MULYA KABUPATEN MERAUKE - Parjono Parjono; Eko Budianto; Adik Putra Andika (Musamus University, 2021)
Post-harvest handling of rice, especially in the rainy season, often experiences problems due to changes in weather, so that it takes a long time. In addition, conventional drying by drying using sunlight often causes the grain to become wet, moist, and some even grow. This causes the rice to break during milling so that it does not meet the quality standards of rice and the price decreases. If this process is disrupted, the level of stability of rice productivity and the supply of rice to the community will be delayed, which in turn will disrupt food security. A rice dryer with UV (Ultra Violet) Dryer technology can be a solution that can be used during the rainy and dry seasons. This tool is a dryer building measuring 10 m x 21 m, 3 m high, with a tool capacity of 10 tons, polycarbonate roof, galvanized pipe frame, and cast floor. The method of implementing PTDM activities, is socialization activities, design, preparation of materials, labor, implementation of assembly, and construction. The result of the socialization activity, is the application of dryer technology, really helps farmers in post-harvest handling, especially in the rainy season. It is hoped that the existence of this UV Dryer rice dryer can help post-harvest handling of rice and become a model for the community